2014
DOI: 10.1111/joop.12056
|View full text |Cite
|
Sign up to set email alerts
|

Directionality of the associations between psychological empowerment and behavioural involvement: A longitudinal autoregressive cross‐lagged analysis

Abstract: Many cross‐sectional studies have suggested that psychological empowerment (PE) – a higher‐order motivational construct – is related to employees' in‐role and extra‐role behavioural involvement (BI). The objective of this study was to assess the directionality of the longitudinal relationships between PE and employees' BI. Based on theories, three alternative causal directions are examined: two unidirectional models (PE → BI, BI → PE) and one reciprocal model including effects in both directions. A total of 81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 82 publications
4
41
0
2
Order By: Relevance
“…Likewise, Boudrias et al . () provided evidence for a positive longitudinal effect of the distinct dimensions of psychological empowerment on those of behavioural empowerment. However, this is the first study to extend these results to the healthcare context by showing that psychologically empowered nurses' are more likely to effectively perform their work tasks and to make proactive efforts aimed at improving current ways of doing things.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Likewise, Boudrias et al . () provided evidence for a positive longitudinal effect of the distinct dimensions of psychological empowerment on those of behavioural empowerment. However, this is the first study to extend these results to the healthcare context by showing that psychologically empowered nurses' are more likely to effectively perform their work tasks and to make proactive efforts aimed at improving current ways of doing things.…”
Section: Discussionmentioning
confidence: 95%
“…Boudrias et al . ). In this study, the fit indices for the five first‐order factors plus one second‐order factor indicated an acceptable fit (χ 2 [385] = 621·71, CFI = 0·93, RMSEA = 0·06, SRMR = 0·07).…”
Section: The Studymentioning
confidence: 97%
See 3 more Smart Citations